Experience sampling methods require more than numbers. - Bringmann, Laura F.; Guðmundsdóttir, Guðrún R.; Schorrlepp, Leonie; Vogelsmeier, Leonie V. D. E.; De Smet, Melissa M.; Vrijen, Charlotte; van Roekel, Eeske; Fritz, Jessica; Chen, Jennifer X.; Kirtley, Olivia; Eronen, Markus I.; Chung, Joanne M.; et al. (Communications Psychology, 2026)
The experience sampling method (ESM) collects people's real-time reports about their feelings, actions, and surroundings. While this method originally included both numerical and open-ended responses, most studies today focus only on the numbers. We argue that ESM researchers should collect and analyze open-ended responses again, as they are crucial for understanding what the numbers really mean, and for capturing parts of experience that numbers alone cannot, such as context, the "why" behind responses, and the temporal order of events. Open-ended responses can improve ESM data by grounding it in real-world experiences and phenomena as they are experienced in everyday life. Therefore, handbooks and guidelines on ESM should again include dedicated sections on collecting and analyzing open-ended text items. We highlight future work that is needed to achieve the systematic integration of open-ended items and their analysis into ESM research. The experience sampling method (ESM) collects real-time reports of people's feelings, actions, and surroundings, and originally included both numerical and open-ended responses. Whereas most studies today focus only on the numbers, we argue that open-ended responses should be collected and analyzed again, because they are essential for understanding what the numbers mean and for capturing context and the temporal order of experiences.